Vitamin D supplementation in pregnancy and early infancy in relation to gut microbiota composition and C. difficile colonization: implications for viral respiratory infections. Issue 1 (9th November 2020) - Drall, Kelsea M.; Field, Catherine J.; Haqq, Andrea M.; de Souza, Russell J.; Tun, Hein M.; Morales-Lizcano, Nadia P.; Konya, Theodore B.; Guttman, David S.; Azad, Meghan B.; Becker, Allan B.; Lefebvre, Diana L.; Mandhane, Piush J.; et al.
ABSTRACT: In Canada and the US, the infant diet is supplemented with vitamin D via supplement drops or formula. Pregnant and nursing mothers often take vitamin D supplements. Since little is known about the impact of this supplementation on infant gut microbiota, we undertook a study to determine the association between maternal and infant vitamin D supplementation, infant gut microbiota composition and Clostridioides difficile colonization in 1, 157 mother-infant pairs of the CHILD (Canadian Healthy Infant Longitudinal Development) Cohort Study over 2009–2012. Logistic and MaAsLin regression were employed to assess associations between vitamin D supplementation, and C. difficile colonization, or other gut microbiota, respectively. Sixty-five percent of infants received a vitamin D supplement. Among all infants, infant vitamin D supplementation was associated with a lower abundance of genus Megamonas (q = 0.01) in gut microbiota. Among those exclusively breastfed, maternal prenatal supplementation was associated with lower abundance of Bilophila (q = 0.01) and of Lachnospiraceae (q = 0.02) but higher abundance of Haemophilus (q = 0.02). There were no differences in microbiota composition with vitamin D supplementation among partially and not breastfed infants. Neither infant nor maternal vitamin D supplementation were associated with C. difficile colonization, after adjusting for breastfeeding status and other factors. However, maternal consumption of vitamin-D fortified milk reduced the likelihood of C. difficile colonization in infants (adjustedOR: 0.40, 95% CI: 0.19–0.82). The impact of this compositional difference on later childhood health, especially defense against viral respiratory infection, may go beyond the expected effects of vitamin D supplements and remains to be ascertained.